Plakat-gazeta Izogiza, n. 40 (ОГИЗ - ИЗОГИЗ (Izogiz), 1968)
Photo montage of Lenin speaking, photographs of October revolution, and photocopies of declarations, on the left. Map of Red Army control of Russia in the civil war with annotations of enemy armies Original title: Плакат-газета Изогиза, n. 40 PO-0775